P‐81: Image Sticking Analysis by Microscopic Intensity Difference in Multi‐domain Pixels. Issue 1 (30th May 2018) - Lo, Shing-Ping; Chen, Li-Min; Fang, Yen-Wen; Lin, Chi-He; Hsu, Wei-Ting; Chiu, Lin Hsuan
Abstract : In this paper, we employ a novel method to analyze image sticking in microscopic areas of the liquid crystal displays (LCDs). After stressing the display by black and white pattern for a period of time, we found that the microscopic intensity measurement results in sub‐pixel can well link to image sticking phenomenon. Moreover, specific area of pixels gives more contribution to image sticking issue.